Serological IgM antibody profile of M. Leprae PGL-1 and characteristics of leprosy contacts from an endemic area in East Java, Indonesia - Retno Adriyani; Chatarina U. Wahyuni; Ririh Yudhastuti; Mahmudah Mahmudah; Hari B. Notobroto; Iswahyudi Iswahyudi; A. D. Adriaty (AOSIS, 2023)
Background: Indonesia has the third-highest leprosy prevalence, and the transmission continues. Objectives: The present study aimed to describe some of the characteristics of leprosy contacts, such as the profile of the serological antibody IgM anti-PGL-1, socioeconomic factors, environmental factors, and behavioral factors. Materials and Methods: We conducted a cross-sectional study involving 77 leprosy contacts from an endemic area in Winongan, Pasuruan, East Java, Indonesia. The households or neighbors of the leprosy case recorded at Winongan Health Center, voluntarily participated in this study. Informed consent was obtained before starting the study. Three of them were excluded because they showed skin lesions as leprosy symptoms. Serum samples were assayed for IgM antibodies PGL-1 titers using enzyme-linked immunosorbent assay (ELISA). The questionnaire was used to collect information about demographic, socioeconomic, environmental, and behavioral aspects of contact. The data were analyzed descriptively using Fisher's Exact Test. Results: Of 74 contacts, all of them were contacts of MB cases, and 6 (8.11%) were seropositive, with a cut-off point ≥ 605 ug/ml. Although none of the contact characteristics were significantly associated with IgM anti-PGL-1 seropositivity, potential risk markers and indirect transmission of leprosy were identified, including 56.76% manual labor, 90.54% living in poverty, 83.78% drinking from unprotected springs, only 20.27% boiling water to drink, and 48.65% bathing in open water bodies. Conclusions: The seropositivity among contacts, especially perimeter contacts, may identify potential active infection and transmission of leprosy in this population. Identified potential risk markers of leprosy should be noticed for prevention programs supporting leprosy elimination.